Research on Disney’s Marketing Strategy - Wang, Ru (Transactions on Economics, Business and Management Research, 2024)
Disney, leveraging its profound cultural foundation, diversified product matrix, and global operational model, has built a global entertainment empire spanning multiple sectors, including film, theme parks, and consumer products. This paper delves into five core elements of Disney’s marketing strategy: brand extension, content innovation, global expansion, emotional resonance marketing, and the process of digital transformation. The aim is to explore how Disney maintains its leading position in the highly competitive global market while flexibly adapting to rapid changes in the market environment. Additionally, this paper examines the challenges and shortcomings Disney faces in its marketing efforts and offers a series of suggestions for optimizing strategies and improving outcomes to help Disney continue to shine in its future development.